2014
DOI: 10.1111/tct.12148
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional learning for medication safety

Abstract: The majority of the workshops were facilitated by an interprofessional team comprised of pharmacists, doctors and nurses, with all students working in small groups with participants from each of the professional groups, where possible. All seminars had standardised materials, but it was up to individual facilitators to choose which of the five case studies were used within the seminar. The seminars lasted between 2 and 3 hours, and depending on which case studies were used, two or three cases could be discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 8 publications
0
27
0
3
Order By: Relevance
“…Although this method is quite effective for use in a single discipline, it has been shown that multi-disciplinary small group workshops that are implemented toward the end of a health care professional degree program can be of greater benefit, particularly enabling better teamwork and communication. 7,8 However, implementing multi-disciplinary education, particularly at a senior student level, can be problematic due to the resource and logistic challenges it presents. 9 Peer-led education is another non-didactic approach to learning that has been used in training health care professionals and students in a number of areas.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is quite effective for use in a single discipline, it has been shown that multi-disciplinary small group workshops that are implemented toward the end of a health care professional degree program can be of greater benefit, particularly enabling better teamwork and communication. 7,8 However, implementing multi-disciplinary education, particularly at a senior student level, can be problematic due to the resource and logistic challenges it presents. 9 Peer-led education is another non-didactic approach to learning that has been used in training health care professionals and students in a number of areas.…”
Section: Introductionmentioning
confidence: 99%
“…11,[20][21][22][24][25][26]28,32,35,36,[38][39][40]42 For the rest, three studies each were conducted in the UK and Canada, two in Australia and one each in Sweden, Malaysia, the Philippines, China and Switzerland. 6,17,19,23,27,[29][30][31]33,34,37,41,43 Nine main strategies were identified for executing IPE activities: simulation-based education programmes; rotations in rural and community settings; interprofessional training wards; patient-centred case studies; theme-centred workshops; student seminars; student-delivered lectures; health promotion activities; and interactive lectures in a common setting. 6,11,17, Many of the institutions implementing IPE had not restricted themselves to one strategy and instead supplemented the aforementioned activities with additional teaching/ learning methods.…”
Section: Resultsmentioning
confidence: 99%
“…33,41 Theme-centred workshops conducted by students working in small interprofessional groups were also reported. 26,28,30,31,40 These interactive teaching sessions promote critical thinking and effective communication as the students taught each other about various aspects of cases in small-group settings. Additional methods for imparting IPE included interprofessional student seminars, roleplaying and lectures from invited speakers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odegard et al identified some practical issues associated with implementing and sustaining IPE sessions including the need for an appropriate physical space 18. Issues such as differences in curricula, scheduling, and intended learning outcomes also need consideration with potential solutions having been suggested 8,18…”
Section: Introductionmentioning
confidence: 99%